Utilização de ninhos artificiais por vertebrados e invertebrados, em um fragmento de mata Atlântica no sul do Brasil - Figueiredo, Nícolas de Souza Brandão de (2015)
Tree cavities are an important natural resource found in many habitats, providing breeding sites and shelter for arthropods, birds and mammals. However, nest boxes have been more frequently used in Brazil as a tool aiming the conservation of endangered psittacids. In view of this fact, the general objective of the present dissertation was to verify how the use of the artificial tree cavities by vertebrates and invertebrates occurs. In this study we tested the following hypotheses: 1) due to a possible lack of natural cavities at the forest edge, there will be a greater use of the artificial cavities at the edge than inside; 2) there will be an increased use of the artificial cavities by the exotic species at the edge than inside; 3) because there are natural predators, native species should prefer little depth nests and nests with small openings; 4) due to the edge effect, there will be a decline in the availability of natural cavities of the interior in the edge direction and 5) in transects with lower availability of natural cavities, there will be a greater use of the nest boxes. To carry out this work, we selected a subtropical Atlantic forest fragment, with an area of 80 ha, located in Santa Maria, Rio Grande do Sul, Brazil. Ten transects were established (five in edge and five inside the fragment), in which 120 artificial nests were hung (60 nests on the edge and 60 inside). The nests were installed in August 2013 and monitored every six days, between September and December 2013 and between September and December 2014. In order to allow the use of the nests by various groups of animals, these nests were made with medium and large-sizes (20 x 30 cm base and 30 cm high x 45 cm), with little or great depth (opening at the top or in the middle of the nest) and small openings (5 cm diameter), medium (10 cm) and large (15 cm). Inside the fragment, there were 29 uses and in the edge 31 uses. Hymenoptera was the most frequent group, corresponding to 61.40% of the occupations (35 of the 60 occupied boxes). Araneomorphae was the second most frequent group with 13 occupied nests; nine nests were occupied by birds (generating 17 chicks, 16 of Pyrrhura frontalis and a chick of Dendrocolaptes platyrostris). Mammals were the least frequent group with only three used boxes (two nests occupied by Didelphis albiventris and one by Guerlinguetus sp.). It was also observed a greater availability of natural cavities inside (50) than at the edge (14), which was considered significant through the statistical test of Mann-Whitney, since the p value was 0.047. Generally the native species sought more cavities with small and little depth openings, while the exotic species (A. mellifera) proved generalist. It was verified, therefore, that it was more difficult for birds and mammals to accept artificial cavities in a short time while the exotic species has demonstrated a rapid acceptance of these structures.